The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1128/mcb.23.4.1221-1230.2003
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Meprin β Gene in Mice Leads to Underrepresentation of Knockout Mice and Changes in Renal Gene Expression Profiles

Abstract: Meprins are multidomain zinc metalloproteases that are highly expressed in mammalian kidney and intestinal brush border membranes and in leukocytes and certain cancer cells. Mature meprins are oligomers of evolutionarily related, separately encoded ␣ and/or ␤ subunits. Homooligomers of meprin ␣ are secreted; oligomers containing meprin ␤ are plasma membrane associated. Meprin substrates include bioactive peptides and extracellular matrix proteins. Meprins have been implicated in cancer and intestinal inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 36 publications
(55 reference statements)
1
54
0
1
Order By: Relevance
“…In fact, meprin ␣ is implicated in the cellular transmigration events of metastatic colon cancer cells, because these cell lines selectively express meprin ␣, and nonmetastatic colon cancer cells are meprin ␣ Ϫ (G. Matters, unpublished observations). Interestingly, in mice, active meprin ␣ is localized with meprin ␤ to the apical surface of the proximal tubular epithelium, while the secreted form of meprin ␣ is inactive and forms meprin ␣ homo-oligomers (5,19). Whatever the mechanism, it can be concluded that meprin ␤ is essential to leukocyte infiltration, at least in vitro in the mesenteric lymph node.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, meprin ␣ is implicated in the cellular transmigration events of metastatic colon cancer cells, because these cell lines selectively express meprin ␣, and nonmetastatic colon cancer cells are meprin ␣ Ϫ (G. Matters, unpublished observations). Interestingly, in mice, active meprin ␣ is localized with meprin ␤ to the apical surface of the proximal tubular epithelium, while the secreted form of meprin ␣ is inactive and forms meprin ␣ homo-oligomers (5,19). Whatever the mechanism, it can be concluded that meprin ␤ is essential to leukocyte infiltration, at least in vitro in the mesenteric lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…Meprin ␤ null and wild-type mice were generated on a C57BL/6:129/SvJ background and characterized (19). Leukocytes from the mesenteric lymph nodes from 3-mo-old meprin ␤ null mice and strain/age-matched wild-type mice were isolated, as described above.…”
Section: Chemotaxis and Invasion Assaysmentioning
confidence: 99%
“…Along with the phenotype of Mep1a −/− and Mep1b −/− mice at the histological level, the observed reduced levels of procollagen I conversion in skin and primary fibroblasts isolated from meprin KO mice provide further evidence that meprin α and meprin β exhibit PCP activity in vivo. Interestingly, significantly fewer Mep1b −/− mice (∼50%) are born compared with WT mice, indicating essential functions of this protease already during early embryonic development (43). Moreover, morpholino-induced meprin knockdown in zebrafish embryos revealed severe defects in organogenesis and tail morphology, which also might be linked to reduced collagen fibril assembly in these animals (15).…”
Section: Discussionmentioning
confidence: 99%
“…The generation of Mep1b 2/2 mice has been described in Norman et al (33). Mice were kept in specific pathogen-free conditions in isolated ventilated cages, with a 12-h light-dark cycle and food and water provided ad libitum.…”
Section: Animalsmentioning
confidence: 99%